Rock on record - Zak, Albin (State University of New York Press, 2022)
An introductory textbook for Rock Music Appreciation and History courses, Rock on Record traces the story of rock from the late 1940s through the pre-rock styles of the 1950s to rock in its heyday in the 1960s and, then follows its continued growth in the 1970s and early 1980s. Rock on Record puts listening first, teaching students how to listen to key recordings in the rock repertoire. The book opens with general guidance on how to listen to a recording as well as an overview of the song structures commonly used by rock songwriters. Then, in twenty-two chronological sections, Albin J. Zak provides historical context for each new genre or style, discussing its key recordings and performers and its impact on the artists who followed. Zak analyzes seventy-three recordings using easy-to-follow listening guides, giving students the tools they will need to enhance their enjoyment and understanding while also highlighting a wide range of examples that illustrate the richness of the rock repertory. Rock on Record examines how rock changed American culture and encourages students to explore further on their own.